(untitled) (Contemporary Journal of Social Science Review, 2025)
Transhumanism represents a contemporary intellectual movement advocating the use of advanced technologies, such as artificial intelligence, biotechnology, genetic engineering, and cybernetics, to enhance human physical, cognitive, and psychological capacities. While these ideas have gained significant traction in Western philosophical and scientific discourse, their ethical evaluation within Islamic societies remains limited and fragmented. This article offers a comprehensive Islamic ethical analysis of transhumanism, drawing upon classical Islamic sources, contemporary Muslim scholarship, and expert discourse emerging from Pakistan. It argues that Islam neither rejects technology outright nor accepts human enhancement unconditionally. Instead, it provides a principled framework grounded in fitrah (human nature), maqāṣid al-sharīʿah (objectives of Islamic law), maṣlaḥah (public interest), and ijtihād (independent reasoning). The study concludes that therapeutic and life-preserving technologies may be permissible under strict ethical conditions, whereas enhancement-oriented and immortality-driven transhumanist aspirations fundamentally conflict with Islamic theology and moral anthropology.